1988
DOI: 10.1071/bi9880279
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Exogenous Growth Hormone: Effects on Milk Production and Utilization of Nutrients in Muscle and Mammary Tissues of Lactating Ewes

Abstract: Exogenous bovine growth hormone at a dose of 0·1 mg kg-1liveweight increased yields of milk and milk constituents and milk fat content when injected over 5 days into ewes in mid-lactation. These changes in milk production were associated with changes in the supply to, and utilization of, nutrients by leg muscle and mammary tissues.Arterial concentrations of glucose and non-esterified fatty acids increased significantly, concentrations of lactate and 3-hydroxybutyrate tended to increase, and concentrations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
(37 reference statements)
2
9
1
Order By: Relevance
“…In this respect the present results are consistent with results of previous short-term studies with sheep (Dracy and Jordan 1954;Jordan and Shaffhausen 1954;Hart et al 1985;McDowell et al 1988), goats (Hart et al 1983;Mepham et al 1984) and dairy cattle (see McCut~heon and Bauman 1985;McDowell 1985;Johnsson and Hart 1986). Similarly, the present results with sheep are in conformity with results of previous longterm studies with dairy cows Peel et al 1985;Chalupa et al 1987).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this respect the present results are consistent with results of previous short-term studies with sheep (Dracy and Jordan 1954;Jordan and Shaffhausen 1954;Hart et al 1985;McDowell et al 1988), goats (Hart et al 1983;Mepham et al 1984) and dairy cattle (see McCut~heon and Bauman 1985;McDowell 1985;Johnsson and Hart 1986). Similarly, the present results with sheep are in conformity with results of previous longterm studies with dairy cows Peel et al 1985;Chalupa et al 1987).…”
Section: Discussionsupporting
confidence: 82%
“…1984) when administered over short periods of several days. In such short-term studies it has been shown 0004-9417/88/030357$03.00 that nutrient utilization in the body as a whole McDowell et al 1987b) and in muscle and mammary tissues (McDowell et al 1987a(McDowell et al , 1988 is altered by GH so as to increase the supply of nutrients for milk synthesis as was suggested originally by Bauman and Currie (1980) and Bines and Hart (1982).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations